GROSS SKIN THICKNESS IN RELATION TO AGE IN DIFFERENT REGIONS OF BAKERWALI GOAT - Raheeqa Razvi; Shalini Suri; Kamal Sarma (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted to record the gross thickness of skin in various regions of the body at different age groups on Bakerwali goats. The animals were divided into three age groups viz, neonatal, young and adult. The thickness of skin increased with advancement of age. Neck dorsal showed the maximum thickness and thorax ventral showed the minimum thickness among the different regions in all the groups studied.